Modification of the Predicted Heat Strain (PHS) model in predicting human thermal responses for Chinese workers in hot environments. (November 2019) - Du, Chenqiu; Li, Baizhan; Li, Yongqiang; Xu, Mengnan; Yao, Runming
Abstract: The Predicted Heat Strain (PHS) model predicts physiological responses of European people to heat stress; while its performance for Chinese population remains underexplored. The study conducted a heat exposure experiment (temperature: 35 °C/38 °C/40 °C, relative humidity (RH): 25%/40%/60%) in a well-controlled climate chamber. 10 male Chinese workers were recruited to perform exercises on the treadmill at a speed of 0.5 m/s for 120min, to simulate moderate metabolic rate. Rectal temperature(Tre), skin temperature(Tsk), sweat rate(SR) and heart rate(HR) were monitored continuously; the corresponding predicted values were obtained by the PHS model. The results showed that the measured Tre, Tsk, SR increased significantly with increased temperature and RH. The PHS model overestimated the maximum allowable exposure time of subjects but underestimated the final Tre and Tsk. Bland–Altman analysis showed that the differences and 95%CI between the observed and predicted values increased with increasing temperature, RH and exposure time, indicating the significant prediction deviation of the PHS model. Through adjusting the initial Tre from 36.8 °C to 37 °C, the protection efficacy was improved from original 24.7% to57.1% for the PHS model. The protection efficacies were further improved to 71.2% through adjusting the maximum HR based on ages, and to 68.2% through adopting the real-time HR to predict metabolic rates. The proposed three methods improve the heat strain prediction in the PHS model for Chinese workers and are more applicable in practical hot working place. This benefits to policy decisions and occupational safety protection for Chinese workers with heat exposure risks. Highlights: Performance of PHS model for Chinese worker is examined by experiments. Exposure times of workers were overestimated by PHS model in hot environments. Tre and Tsk are underestimated and SR are overestimated using Bland-Altman analysis. Protective efficacy is improved by modifying initial Tre, max HR and real time HR. The modified PHS model predicts heat strain with higher accuracy.